INTEGRASI MEDIA DIGITAL BERBASIS QR CODE UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN PAI PADA SISWA SMP NEGERI 1 MOJOAGUNG - Khusnul Abidah Ilmi; Emi Lilawati; Mohammad Saat Ibnu Waqfin (Universitas Islam Lamongan, 2025)
The focus of this research is to find out how the use of QR Code digital media can improve the quality of students' PAI learning at SMP Negeri 1 Mojoagung. This research uses a quantitative descriptive approach, with stages of observation, interviews, questionnaires and documentation. Learning quality is the component studied, which includes student satisfaction with the use of QR Code-based digital media, student motivation and engagement, impact on student understanding, and implementation difficulties. Students in class VIII A of SMP Negeri 1 Mojoagung are the subjects of this research. The research results show that the use of QR Code-based digital media in PAI learning helps students. This is because this media is considered fast, easy to understand and practical to use, making it more interesting compared to conventional learning media. Students also hope that QR Code-based digital media will be created for other subjects so that their enthusiasm for learning, quality of learning and learning outcomes will increase. After students answer the questionnaire, data is collected. This shows that 32 students averaged a score of 57 with a percentage of 75%. Therefore, the questionnaire results can be categorized as having an average score of 61%–80%, which means good. This research found that QR Code-based digital media can significantly improve the quality of learning if there is adequate infrastructure support.